Changes toward sustainability in consumer purchasing behaviour of everyday products - Irena Baláková; Michal Pšurný; Jana Stávková; Veronika Švecová (Entrepreneurship and Sustainability Issues)
This study aims to identify the factors that influence sustainable consumer purchasing behaviour in the food and everyday products market, which can be used to influence consumer purchasing patterns toward sustainable consumption. The factors commonly observed to influence purchasing decisions, such as price, quality, packaging, and brand, were complemented by factors such as sustainable production, nutritional composition, health benefits, and the product's origin. These additional factors also exert a significant influence on consumer purchasing decisions. A principal component analysis (PCA) identified four determinants of sustainable consumer purchasing behaviour (Product Features, Environmental Responsibility, Comfort and Accessibility, and Pricing). The influence of determinants on real, sustainable purchasing behaviour is evaluated using a PLS-SEM model. The PLS-SEM structural modelling demonstrated a significant impact of all determinants on real, sustainable purchasing behaviour. The first determinant (Product Features) indicates that an individual's rational behaviour is related to sustainability. These variables relate to product quality, nutritional composition, origin, health benefits, and product breadth. Additionally, they reflect attitudes toward life values and norms. Determinant Environmental Responsibility reflects the importance of sustainable practices by both manufacturers and retailers as perceived by consumers. Determinant Comfort and Accessibility encompass the variables most influenced by those who create the external shopping environment, control the marketing tools, and sellers that address the customer (point of sale, accessibility, loyalty to the chain, etc.). The last determinant (Pricing) represents rational decision-making and is subject to the consumer's financial circumstances